Violent Dynamics: Exploring Responsibility-Attribution for Harms Inflicted During Spontaneous Group Violence - Du Bois-Pedain, Antje (Oñati Socio-Legal Series, 2016)
Violent encounters between groups of individuals often leave one or more of the participants dead, and it may be clear from the evidence that the physical cause of death was set by the single, deliberate act of one of the participants only. When this happens, the question arises whether, and how, responsibility for the fatal act and/or for its consequences can be attributed to other participants in the punch-up. Criminal law has long sought - and found - ways of holding others apart from the direct agent responsible for the harms caused in such encounters, although the legal constructions used differ between legal systems and often change significantly over time even within the same jurisdiction. This paper investigates the appropriateness of different criminal-law responses to these cases from two directions: first, by exploring the possible doctrinal grounds within the criminal law for attributing responsibility for the fatal act/outcome to all participants; and then by investigating the extent to which these responsibility-ascriptions are supported or challenged by insights from psychological studies of group action.